2014
DOI: 10.1137/130910932
|View full text |Cite
|
Sign up to set email alerts
|

Almost Optimal Lower Bounds for Problems Parameterized by Clique-Width

Abstract: Abstract. We obtain asymptotically tight algorithmic bounds for Max-Cut and Edge Dominating Set problems on graphs of bounded clique-width. We show that on an n-vertex graph of clique-width t both problems (1) cannot be solved in time f (t)n o(t) for any function f of t unless exponential time hypothesis fails, and (2) can be solved in time n O(t) .Key words. exponential time hypothesis, clique-width, max-cut, edge dominating set AMS subject classifications. 05C85, 68R10, 68Q17, 68Q25, 68W40 DOI. 10.1137/1309… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…A subset of the authors of the current paper, together with Fomin [20], showed that the EDS, HP, and GC problems parameterized by cliquewidth are all W[1]-hard. In particular, this implies that these problems do not admit algorithms with running times of the form O(g(k) · n c ), for any function g and constant c independent of k, unless FPT=W [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of the authors of the current paper, together with Fomin [20], showed that the EDS, HP, and GC problems parameterized by cliquewidth are all W[1]-hard. In particular, this implies that these problems do not admit algorithms with running times of the form O(g(k) · n c ), for any function g and constant c independent of k, unless FPT=W [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this implies that these problems do not admit algorithms with running times of the form O(g(k) · n c ), for any function g and constant c independent of k, unless FPT=W [1]. However, the lower bounds of Fomin et al [20] did not rule out non-trivial improvements to the exponent f (k) of n in the running times.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we prove that Hamiltonian Cycle can be solved in time n O(k) , thereby resolving the open problem in [9]. A Hamiltonian cycle in a graph is a cycle containing all vertices of the graph.…”
Section: Introductionmentioning
confidence: 92%
“…This question has been carefully answered by Fomin et al [8,9]. In particular, they showed that for Max-Cut and Edge Dominating Set, there is no f (k) · n o(k) -time algorithm unless the Exponential Time Hypothesis (ETH) fails, and proposed for both problems algorithms with running time n O(k) .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, we obtain an analogous result to Corollary 3 for rows using the following result. Fomin et al [16] showed that the MaxCut problem can be solved in time O(n 2t+O (1) ) where t is clique-width of the input graph. By the combination of their result and our upper-bounds on clique-width (Theorem 21 in Sect.…”
Section: Corollary 3 the Size Of A Maximum Cut In The Graph Class Defined By U-bubble Models With K Columns Can Be Determined In Timementioning
confidence: 99%